Os mapas insertos nas descrições e guias de viagem a Portugal editados nos séculos XVIII e XIX - Martins, Luís Paulo Saldanha (2017)
The inclusion of maps in travel guides became popular from the second quarter of the nineteenth century, especially with publishers such as Murray or Baedeker, while their diffusion was been significant from the middle of the century.Although there are similarities to previously published works, emphasizing the symbolism of social differentiation of the grand tour, these guides constitute a new period, with a new informative framework geared towards new audiences, from the "tourist" to the ascending middle bourgeoisie. This informational panoply, even by the inclusion of maps of support to the proposed itineraries - of great or small scale - distinguishes both the previous period as the more selective and specialized phase that follow.In a synoptic way, these guides reveal the modernity arising from the sediment of the naturalistic spirit, spread by protobotanists and protozoologists, but also the romantic matrix of sensitive knowledge, which reveals peculiarities and aesthetic landscaping, diversity of customs or confer identity to the multiplicity of peoples and nations.It is intended to carry out a characterization of maps included in guides, many available in virtual libraries, seeking to scrutinize the place they had in the narratives about Portugal as a travel destination. Although with the necessary ramblings, as at least two editors published travel guides about twenty years apart (1864/1887 and 1869/1889), we proceed to the scrutiny of the foundations that may possibly justify the reason and why editors include different maps - in the rigor and diversity of information - in the various publications.